Essentialism and Grounding - Cantero Flores, Víctor (Universidad de Costa Rica, 2018)
It has been claimed that the notions of essence and grounding, in their respective debates, are primitive, neither reducible to nor analysable into any other more basic notion. However, there seems to be interesting connections between them. And these connections are the ones I want to make explicit in this paper. And more specifically, I want to discuss what Gideon Rosen calls the principle of Mediation: if the fact A is grounded in the fact B, then it lies in the nature of the things A and B, that A is so grounded. A difficulty for this principle is considered: the possibility of Moorean connections, that is, the possibility of some general principles that say that certain facts are grounded in some other facts, but cannot be explained by appeal to the essence of the things occurring in those facts. In light of these Moorean connections, I try to clarify the role the notion of essence has in an account of what grounds grounding relations.